Community Acceptance of Digital ZIS Payment Technology: Evidence from BAZNAS Tangerang Selatan City - Deni Nuryadin; Indupurnahayu Indupurnahayu; Didin Hafidhuddin; Irfan Syauqi Beik (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
The acceptance of digital zakat technology is important to be researched, especially on the factors that affect the intention of users of online zakat applications which ultimately leads to the decision to use the application. This study examines factors influencing the intention and decision of muzakki to adopt digital zakat platforms at BAZNAS South Tangerang City. By using the Unified Theory Acceptance and Use of Technology (UTAUT) model with four variables, including performance expectation, effort expectation, social influence and facilitating conditions as well as expanding the model by adding variables such as hedonic motivation, price value, habit, perceived risk, and zakat knowledge. Using a sample of 198 respondents from BAZNAS South Tangerang City, the data that has been collected is analyzed using the Structural Equation Modelling (SEM) method. The results of the analysis found that the variables of the UTAUT model were not a significant factor that affected the intention of the muzakki to decide to use the online zakat application. Meanwhile, the variables of the expansion of the model are a significant factor that affects the intention and decision of muzakki to use online zakat. Keywords: UTAUT, SEM, BAZNAS, sharia fintech